2021
DOI: 10.1002/fsn3.2493
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and odds of breast cancer: A case–control study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Inflammatory dietary patterns, including high intakes of sugary soft drinks, refined grains, red and processed meat, margarine and other hydrogenated fats, and low intakes of green leafy vegetables, cruciferous vegetables, coffee, increased the risk of BC in premenopausal and overweight postmenopausal women (40)(41)(42)(43)(44). In addition, a low dietary inflammation index reduced the risk of BC in obese women (45,46). However, there was no significant relationship between the dietary inflammation index and the incidence rate of BC in a Spanish study (47), while a French study found that an inflammatory diet only increased the risks of ER+, PR+, or HER2+ breast tumor subtypes, but found no relationship with triple-negative (ER-, PR-, and HER2-) BC (48).…”
Section: Dietary Patterns and The Risk Of Bcmentioning
confidence: 99%
“…Inflammatory dietary patterns, including high intakes of sugary soft drinks, refined grains, red and processed meat, margarine and other hydrogenated fats, and low intakes of green leafy vegetables, cruciferous vegetables, coffee, increased the risk of BC in premenopausal and overweight postmenopausal women (40)(41)(42)(43)(44). In addition, a low dietary inflammation index reduced the risk of BC in obese women (45,46). However, there was no significant relationship between the dietary inflammation index and the incidence rate of BC in a Spanish study (47), while a French study found that an inflammatory diet only increased the risks of ER+, PR+, or HER2+ breast tumor subtypes, but found no relationship with triple-negative (ER-, PR-, and HER2-) BC (48).…”
Section: Dietary Patterns and The Risk Of Bcmentioning
confidence: 99%
“…Hammad S, et al 11 Estudo caso-controle Investigar a associação entre os escores índice inflamatório dietético (IID) e câncer de mama (BrCA) entre mulheres jordanianas.…”
Section: Tipo De Estudo Objetivo Geral Do Estudo Principais Resultadosunclassified
“…Hayati et al specified that increased E-DII (Energy Adjusted Dietary Inflammatory Index) scores showed a substantial increase in BC risk by 87% [ 63 ]. However, a study done in Jordan found significant correlation only in obese/overweight individuals where the risk of breast cancer increased by 77% (95%CI 1.01–3.12) when the adherence to the pro-inflammatory diet was highest [ 64 ]. All of these studies are in line with Non-Middle Eastern studies which have shown to increase the risk significantly [ 65 , 66 ].…”
Section: Dietary Patternsmentioning
confidence: 99%